(untitled) (KMC Journal, 2024)
This study investigates the influence of digital financial literacy on individual investment behaviour of Nepali investors. In order to explore the influences of digital financial literacy on individual investment behaviour, causal-comparative research design was used and responses from 358 investors were collected through a survey questionnaire. The convenience sampling method ensured statistical reliability and diversity in perspectives. Questionnaires were distributed through various platforms, ensuring anonymity and confidentiality. Descriptive statistics, regression, reliability and correlation were some of the tools used for a thorough study of the data. These methods enabled non-parametric testing and multiple regressions by providing a quantitative comprehension of the variables. The research establishes that digital financial literacy significantly influences investment behaviour in Nepal. The statistical correlation matrix and regression analysis, with an R Square of 0.589, highlight the interconnectedness of digital financial proficiency, financial literacy, financial goal management and individual investment behaviour. Investment behaviour is significantly influenced by financial literacy, digital financial literacy and financial goal management, having the p-value less than 0.05. However, cyber security and awareness did not show a significant relationship with investment behaviour. Policymakers in Nepal are focusing on enhancing digital financial literacy to empower individuals and cultivate a financially literate society. Financial institutions and educators should leverage digital platforms to enhance financial education and prepare individuals for informed investment decisions in Nepal’s evolving stock market landscape. Examining the digital financial literacy of Nepali investors can help in making more informed decisions regarding investments by looking at structures, comparing findings with those from other developing nations and assessing the effects of educational efforts.